2012
DOI: 10.1179/2047773212y.0000000056
|View full text |Cite
|
Sign up to set email alerts
|

Community-based control ofAedes aegyptiby adoption of eco-health methods in Chennai City, India

Abstract: Background: Dengue is highly endemic in Chennai city, South India, in spite of continuous vector control efforts. This intervention study was aimed at establishing the efficacy as well as the favouring and limiting factors relating to a community-based environmental intervention package to control the dengue vector Aedes aegypti.Methods:A cluster randomized controlled trial was designed to measure the outcome of a new vector control package and process analysis; different data collection tools were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(145 citation statements)
references
References 18 publications
4
131
0
10
Order By: Relevance
“…These findings matched the findings of several other studies. 2,[14][15][16] The most prominent benefit however was the satisfaction created by "working together", which was expressed during FGDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings matched the findings of several other studies. 2,[14][15][16] The most prominent benefit however was the satisfaction created by "working together", which was expressed during FGDs.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition to public health costs there is a major economic and social impact in those countries where large epidemics occur. 2 The use of vaccine in controlling dengue has not been available for public health use in the very near future. Therefore, primary prevention of transmission is crucial to decrease the burden of dengue.…”
Section: Introductionmentioning
confidence: 99%
“…Esto se puede explicar debido a que las mujeres jóvenes suelen tener un mejor conocimiento sobre medidas preventivas en estas enfermedades, así como tienen una decisión más rápida sobre la implementación de estas medidas (17)(18)(19) .…”
Section: Discussionunclassified
“…aegypti of implementing communitybased eco-health measures has been examined in Chennai (formerly Madras) in eastern India [56]. This study revealed that environmentally friendly vector control methods like covering water containers, solid waste management and urban 'clean-up' campaigns involving women's groups and school children led to a substantial reduction in the density of dengue vectors.…”
Section: Current Control Measuresmentioning
confidence: 99%